Effect of Lifestyle Modification Intervention on Antimetabolic Syndrome Drug Treatment Requirement of patients with Metabolic-Syndrome- Associated-Disorders at University of Nigeria Teaching Hospital Ituku Ozalla, Enugu - Chijioke, Pascal C.; Okafor, Michael T.; Mbah, Anthony U.; Anakwue, Raphael C.; Ide, Clinton; Arinze, Queen U. (The Nigerian Journal of Pharmacy, 2025)
Background: Lifestyle modification is the process of gradual adaptation of corrective lifestyle habits such as diet, physical activity, and sleep for the prevention and management of various diseases. Metabolic syndrome encompasses disorders underscored by metabolic irregularities. Nearly 25% of the global population is affected by metabolic syndrome-associated disorders (MSADs), which account for most medical outpatient visits and drug prescriptions. As therapeutic adjuncts, lifestyle modification interventions may have a substantial impact on anti-metabolic syndrome drug treatment requirements for control of phenotypic expressions of MSADs. The aim of this study is to determine the combined effect of lifestyle modification on MSADs as therapeutic adjuncts. Materials and Methods: This was a longitudinal study and part of a randomized controlled trial of lifestyle modification intervention for the management of metabolic syndrome-associated disorders approved by the UNTH ethics committee. Collaborating dieticians, medical sociologists, and exercise physiotherapists assigned Lifestyle Modification Scores (LMS) of GOOD=4-5, FAIR=3, and POOR=0-2 to the patients after diet, sleep, and exercise analysis. Anti-metabolic Syndrome Drug Treatment Requirement (ADTR) score was calculated as the total number of defined unitary dosages of anti-metabolic syndrome drugs times adherence +/- 0.1 accordingly for each unitary or decimal increase/decrease from normal values of clinical/laboratory markers of metabolic syndrome-associated disorders. Results: There was no significant reduction of Actual Drug Treatment (AdhRx) and ADTR scores of study participants with good LMS, although the mean of the scores was lower than that of those with bad LMS (P > 0.05). Conclusion: We conclude that ADTR scores are useful and valid tools to assess the impact of lifestyle modification that addresses the aetiopathogenic mechanism in MSADs. This enables differentiation between control of phenotypic expression of MSADs by drugs and that due to lifestyle modification.